Magnesium, boron, and manganese in the zinc uptake by excised roots of two rice cultivars - Moreira, Adônis; Garcia y Garcia, Axel; Heinrichs, Reges; Malavolta, Eurípedes (Semina: Ciências Agrárias, 2003)
The effect of Mg, Mn and B in uptake of 65Zn was studied by using excised roots from the cultivars IAC 165 and IAC 201. The experimental design was a randomized block scheme with three replicates. Two rates of Mg (0.1 and 0.4 mmol L-1) two rates of B (0.1 and 0.4 mmol L-1) and two rates of Mn (0.1 and 0.4 mmol L-1) were assessed in the presence of four zinc concentrations (0.5, 1.0, 2.0 and 10.0 mmol L-1). The results showed that the rice cultivars IAC 165 and IAC 201 in different Mg, B and Mn concentrations in the solution have distinct behavior in Zn uptake. The incresead magnesium rates inhibit the zinc uptake in two cultivars, whereas the boron and manganese rates in the solution incresead Zn uptake by excised roots of rice.